1994
DOI: 10.21000/jasmr94010080
|View full text |Cite
|
Sign up to set email alerts
|

Metal Removal in Wetland Treatment Systems

Abstract: Wetland treatment has successfully removed nickel, copper, cobalt, and zinc from neutral mine drainage in northeastern Minnesota. Pilot and full-scale overland flow wetlands have removed up to 90% of the incoming nickel and 50% to 90% of the other metals. Nickel is the major contaminant in the mine drainage, with average concentrations from 2 to 5 mg/L. The other metals were generally present at concentrations less than 0.1 mg/L. In short-term tests, using drainage that contained around 1 mg/L zinc and 0.4 mg/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…Nickel removal in the test cells and the WID system also decreased in the fall (Eger et al, 1994(Eger et al, , 1996. Winter operation data for other wetland systems · is limited, but year-round copper removal has been reported in British Columbia (Sobolewski et al, 1995) and metal removal was also observed throughout the winter in the Big 5 Tunnel pilot cells in Colorado (Wildeman et al, 1992).…”
Section: Treatmentmentioning
confidence: 95%
See 2 more Smart Citations
“…Nickel removal in the test cells and the WID system also decreased in the fall (Eger et al, 1994(Eger et al, , 1996. Winter operation data for other wetland systems · is limited, but year-round copper removal has been reported in British Columbia (Sobolewski et al, 1995) and metal removal was also observed throughout the winter in the Big 5 Tunnel pilot cells in Colorado (Wildeman et al, 1992).…”
Section: Treatmentmentioning
confidence: 95%
“…Nickel removal was on the order of 90% and the cells were capable of producing water that met water quality standards (Eger et al, 1993(Eger et al, , 1994. Based on these results, LTV designed and constructed two wetland systems in 1992 (Eger et al, 1992, Frostmao, 1992.…”
Section: Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Adding chemicals and energy-consuming treatment processes are nearly eliminated with passive treatment systems. Also, the operational and maintenance costs of passive systems like minimum inputs, low-skilled work such as technical manpower, chemicals, no external power required, reduce operational and maintenance cost [11,12] are significantly less than active treatment systems. The design of a passive treatment system for AMD requires the knowledge of mine water chemistry, available treatment techniques, and experience.…”
Section: B Passive Treatment Of Amdmentioning
confidence: 99%
“…The metal adsorption capacity of wetlands depends on many factors like concentrations of dissolved metals, dissolved oxygen (DO), air, pH, the alkalinity of AMD, active microbial biomass and the retention time of AMD in the wetland [22].The area of the wetland depends on the influent load entering the wetland. Aerobic wetlands are a good option for long-term treatment in low maintenance and operational costs [12], but these wetlands require longer detention time and huge surface area [22] for acid mine water treatment. The major factors that should be taken into account for design of a suitable wetland system vary upon site characteristics, are following: biochemical processes, seasons variation, authoritative issues, substrate, sediment control, the influent acidity loads and retention time ,morphometry , redox state & pH, slope of wetland, vegetation density, rate of flow of water and the land available for a wetland [23].…”
Section: Aerobic Wetlandsmentioning
confidence: 99%